Ultrasound guided direct puncture percutaneous nephrostomy: a single tertiary centre observational study - Rulaniya, Suresh Kumar; Swain, Samir; Neniwal, Vishal Kumar; Bhalothia, Shweta; Tonge, Kishor; Agarwal, Piyush; Khan, Zaid Ahmad; Hota, Datteswar (International Surgery Journal, 2021)
Background: Percutaneous nephrostomy (PCN) is indicated to drain the upper urinary tract collecting system in cases of obstruction. Objective of our study is to evaluate the safety and efficacy of Ultrasound guided direct puncture PCN in our populations. Methods: This observational study was conducted from May 2020 to April 2021in department of urology and renal transplant. The total 65 patients with upper urinary tract obstruction requiring PCN were enrolled. All parameters were recorded and statistical analysis was performed using the Statistical package for the social sciences (SPSS 16.0) for windows. Results: In our study Ca Cervix with ureteric infiltration (35%) was the most common indication for PCN tube placement. Majority of patients (83%) had Grade IV and Grade III hydroneprosis. Single attempt for tube placement was sufficient most of the time in (86% cases). Direct Puncture PCN tube placement was successful in 62 (95.4%) cases. The mean duration of procedure was 12.4 minutes. Loin pain was the most common procedure related complication observed in 58 patients. There was no evidence of visceral injury, no need of blood transfusion in post procedural duration in our study. Conclusions: USG guided direct puncture PCN technique is simple, low cost, less time consuming, less chance of loss of tract and effective procedure for drainage of urine in case of upper urinary tract obstruction. We recommended this procedure in grade III and IV hydronephrosis and this procedure suitable for developing countries like India because of procedure related low cost.